2013
DOI: 10.1039/c3tb20668h
|View full text |Cite
|
Sign up to set email alerts
|

Shell-crosslinked knedel-like nanoparticles induce lower immunotoxicity than their non-crosslinked analogs

Abstract: The development of stable nanoparticles that can withstand the changing conditions experienced in a biological setting and also be of low toxicity and immunogenicity is of particular importance to address the problems associated with currently utilized nanotechnology-based therapeutics and diagnostics. The use of crosslinked nanoparticles continues to receive special impetus, due to their robust structure and high kinetic stability, and they have recently been shown to induce lower cytotoxicity than their non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
(80 reference statements)
0
32
0
Order By: Relevance
“…MCP-1 was the only cytokine that was significantly induced upon treatment with the PEG 5k -SCKs. We have evidence from another study that some cytokines, and in particular MCP-1, were significantly induced upon PEGylation of nanoparticles [32]. However, it is worth mentioning that induction of immunotoxicity depends on the overall nanoparticle composition and it is challenging to attribute a particular toxicity to specific components, due to the unrealistic use of homopolymers as controls, which as noted above, cannot emulate the behaviors of the same materials when assembled within a nanoscopic framework.…”
Section: Resultsmentioning
confidence: 99%
“…MCP-1 was the only cytokine that was significantly induced upon treatment with the PEG 5k -SCKs. We have evidence from another study that some cytokines, and in particular MCP-1, were significantly induced upon PEGylation of nanoparticles [32]. However, it is worth mentioning that induction of immunotoxicity depends on the overall nanoparticle composition and it is challenging to attribute a particular toxicity to specific components, due to the unrealistic use of homopolymers as controls, which as noted above, cannot emulate the behaviors of the same materials when assembled within a nanoscopic framework.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that a nominal 20%-crosslinking of the micelle shell functionalities was more efficient than PEGylation of micelles and PEGylation of the 5%-crosslinked SCKs in reducing the release of cytokines. 146 Immunotoxicity associated with non-crosslinked PEG-micelles highlights the advantages of using crosslinked nanoparticles. In comparison, Lipofectamine ℱ induced significantly higher expression of almost all the tested cytokines as compared to both PDLLA- and polyphosphoester-based nanoparticles, which confirm the usefulness of designing degradable nanomaterials in reducing immunotoxicity.…”
Section: The Design Of Polymer Nanostructures To Address Challengementioning
confidence: 99%
“…23−25 In addition, cellular delivery of nucleic acids has been achieved using shell-cross-linked nanoparticles, and we have initiated a transition from nondegradable polymer nanoparticles (e.g., poly(acrylamidoethylamine)- b -polystyrene)) 26−28 to partially degradable polymer systems (e.g., poly(acrylamidoethylamine)- b -polylactide). 29 With the desire to move toward fully degradable polymer nanoparticle systems, we have recently reported the straightforward synthesis of versatile and degradable polymer platforms making use of polyphosphoester (PPE)-based block copolymers 30−32 and demonstrated their potential use as drug delivery vehicles in biomedical applications, such as the in vivo delivery of paclitaxel 33 and antimicrobial agents to the lungs.…”
Section: Introductionmentioning
confidence: 99%